The Typology of Āmreḍita Compounds in the Ṛgveda - Tamara DITRICH (Acta Linguistica Asiatica, 2011)
Āmreḍita compounds in the Ṛgveda are considered to be a type of coordinative nominal constructions, closely related to dvandva compounds. This article investigates āmreḍita compounds against the background of other coordinative nominal constructions from Ṛgveda 1.1–1.50 which were analysed and compared with their parallel attestations in other maṇḍalas of the Ṛgveda. The first fifty hymns of the Ṛgveda form an organic whole: they belong to the middle period in the Ṛgvedic chronology and address a rich variety of deities, providing a substantial amount of material to address the typological problems of āmreḍita compounds. The article overviews the problems related to the typology of āmreḍita compounds, their analysis in the Ṛgvedapadapāṭha and the Aṣṭādhyāyī, examines all āmreḍita compounds attested in Ṛgveda 1.1–1.50 and compares them with dvandva compounds, noting their interrelations, similarities and differences and consequently, identifies some of their typological features.